Evaluating America's Teachers : Mission Possible?. - Popham, W. (William) James (SAGE Publications, 2013)
When teacher evaluations are fair, everyone wins. Poor evaluation systems don't just hurt teachers-they hurt students, too. That's why America can't afford to wait for the teacher-evaluation problem to be solved. To provide balanced, accurate, and rigorous evaluations that take into account each teacher's particular circumstances, only one system can work: evidence-governed collegial judgment. This book includes: A discussion of common evaluation systems, including testing, value-added models, and observations Analysis of federal guidelines and state responses Action steps teache.